Machining and CNC Technology, Student Text - Fitzpatrick Michael (American : McGraw -Hill, 2003)
This is an introductory machine tools text that assumes students have had no previous machining instruction. Students will learn good machining principles and CNC operations that all machine tools now have as standard equipment. The content of this text fits any equipment and supports any career plan.
Keywords: Machining - Handbooks, manuls; Machine - tools - Numerical control - Handbooks, manuals